APPLICATION OF GLOBAL OPTIMIZATION TECHNIQUE FOR CALIBRATING THE XINANJIANG WATERSHED MODEL - H. A. P. Hapuarachchi; Zhi-jia Li; M. Ranjit; Q. J. Wang (Lowland Technology International, 2001)
The manual calibration process of the Xinanjiang model is extremely difficult and it can be a rather frustating and time consuming exercise for an inexperienced person. Therefore, in recent years, researchers are exploring ways to incorporate 'expert knowledge' of conceptual watershed models into the automatic calibration procedures. Although there are many optimization techniques that can be applied for calibrating the Xinanjiang model, they are still not good enough to find a conceptually realistic and global optimum parameters set for the model. This paper presents a brief introduction to the Xinanjiang model and a research work on application of SCE-UA (Shuffle Complex Evaluation) global optimization technique for calibrating Xinanjiang watershed model using hydrological data of three catchments of different sizes and climatic conditions. Results show that the overall performance of SCE-UA method for calibrating the Xinanjiang model is very good. On the basis of the result derived from the calibration and verification stages, it demonstrates that SCE-UA is capable of finding a global optimum and conceptually realistic parameter set for the Xinanjiang model.